(untitled) (Research, Society and Development, 2025)
Obesity, together with overweight, is recognized by the World Health Organization as a chronic disease, given that it lacks a short-term treatment and has multifactorial origins, such as genetics, poor diet, and sedentary lifestyle. Currently, it has risen to become one of the principal global public health problems. Alongside this, semaglutide (Ozempic®), which was initially developed and approved for the treatment of type 2 diabetes, has over time begun to be used off-label for aesthetic purposes, particularly for weight reduction. This research aims to present a study on obesity and the pursuit of information regarding the indiscriminate and off-label use of Ozempic®. Through a bibliographic review conducted on the PubMed, Scielo, and Google Scholar platforms—complemented by an analysis of the Google Trends database (2014–2024) —the growth and geographic distribution of these practices were investigated. The results reveal Brazil as the leading country in interest in the off-label use of semaglutide (Ozempic®), highlighting search peaks from 2020 onward and a global shortage in supply during 2023. It is concluded that there exists an immense need for more rigorous regulatory policies, educational campaigns regarding the dangers of self-medication for a population with an overly simplistic level of understanding, and the promotion of healthy lifestyles.